CONTROLLING BIOFILM FORMATION BY INHIBITING THE QUORUM-SENSING ACTIVITY OF PSEUDOMONAS AERUGINOSA USING THE ETHANOLIC EXTRACTS OF PIPER NIGRUM (PIPERACEAE) FRUIT, PUNICA GRANATUM (LYTHRACEAE) PERICARP, AND PISUM SATIVUM (FABACEAE) SEED (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Bacterial biofilm formation can cause serious problems in clinical and industrial settings, which drives the development or screening of biofilm inhibitors. Pseudomonas aeruginosa is a well-known pathogen that exhibit biofilm formation through quorum-sensing, which is a bacterial cell-to-cell communication that regulates the production of many virulence factors. The inhibition of biofilm formation is a viable option for bacterial eradication. The antibacterial effect of Piper nigrum is related to the presence of phenolic and flavonoid components. Punica granatum has been reported to possess a wide range of biological actions, with tannins and alkaloids stated to be the reason of its antibacterial property. Pisum sativum, on the other hand, contains various constituents, but the tannins and phenolic compounds stated as responsible for its antibacterial property. The minimum inhibitory concentration using the susceptibility testing of P. nigrum, P. granatum, P. sativum ethanolic extracts were 6.67×10-4 g/mL, 2.1978×10-5 g/mL, and 6.25×10-4 g/mL, respectively. On the swarming assay, P. granatum and P. sativum inhibits swarming motility at concentrations of 2.1978×10-2 up to 2.1978×10-4 g/mL, and 6.25×10-2 to 6.25×10-3 g/mL, respectively. The P. nigrum extract did not inhibit the motility.